Observations sur le Rapport de l'Office de révision du Code civil sur les sûretés réelles - Poudrier-LeBel, Louise; LeBel, Louis (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
The Security Law Committee of the Civil Code Revision Office of the Province of Quebec issued its report late in 1975 ; it advocates fundamental changes in the law of security. According to the Committee, the notion of hypothec should be broadened in Quebec Law. It would become a form of security interest in all kinds of property, moveable or immoveable, corporeal or incorporeal. Legal privileges and construction liens would disappear. The authors comment on the reforms advocated by the Committee. They sommarize their main aspects and some of their effects on existing legal and commercial practices. They suggest a reassessment of the outright abolition of construction liens and discuss some of the problems raised by the regulation of hypothecary recourses in the Report.